Dias, A. et al (2011). From 2D to augmented reality: Findings from a Delphi study on innovative media tool. Information Systems and Technologies - CISTI, 2011 Full paper, pp. 496. Abstract available in IEEE Xplore digital library: http://ieeexplore.ieee.org/xpl/mostRecentIssue.jsp?punumber=5962051 - Dias, Albertina (2018)
Findings of a Delphi research on the challenges of bringing new possible business models, economically efficient and socially effective when exploring the new media tool for enhanced learning based on the technology of augmented reality, the multimedia interactive book.